SDGs-Based Mural Mentoring as an Educational Medium to Increase Sustainable Environmental Awareness Among Junior and Senior High School Students - Ariesa Pandanwangi; Ismet Zainal Effendi; Erika Ernawan; Olga Catherina Pattipawaej; Marisa Rianti Sutanto (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: BPK Penabur Cirebon School had an underused school wall and faced the challenge of transforming it into an artistic feature while creating a welcoming environment. Thirty pupils worked together to create a 16-metre-long mural, and post-activity reflections revealed an increased awareness of environmental sustainability. Purpose of the Study: Improve the creative process among pupils by combining art and education, thereby creating a beautiful and harmonious atmosphere within a supportive environment, whilst the pupils actively participate in the planning, design and painting. Methods: The practical community engagement research is designed to include the following stages: problem identification, planning and collaboration, implementation, reflection, evaluation and reporting and publication of activities via video and scientific publications. Results: This project successfully nurtured the students’ spirit through a sense of togetherness and cooperation, developed their leadership skills in decision-making, and fostered a sense of ownership of the school as their second home. The students successfully transformed bare walls into an artistic, well-organised, integrated and clean environment capable of conveying a powerful message through the theme of harmony. Overall, this project has also enhanced the school’s brand as an institution committed to environmental sustainability, aligned with the SDGs.